Studies on serum lipid profile in hypertensive patient - Sarkar, D; Latif, SA; Uddin, MM; Aich, J; Sutradhar, SR; Ferdousi, S; Ganguly, KC; Wahed, F (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):60-6The abstract of this article is available on the PubMed website